+0  
 
0
549
1
avatar

a=b        /∙a

a^2=ab       /-b^2

a^2-b^2=ab-b^2        factorize

(a-b)(a+b)=b(a-b)       /÷(a-b)

a+b=b        replace the a by a b, as a=b

b+b=b

2b=b         /÷ b

2=1

Q.E.D

Detect the Fallacy

Have fun messing with your friends

Guest Oct 25, 2015
 #1
avatar+1792 
+5

please

 

first line you set a=b

thus (a-b)=0

 

4th line you divide by (a-b), i.e. you divide by 0.  This is undefined.

Rom  Oct 25, 2015

18 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.